1976
DOI: 10.1159/000175693
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Vitamin E Deficiency and Combined Deficiency in Vitamin E and Polyunsaturated Fatty Acids on the Biosynthesis and Degradation of Rat Central Nervous System Myelin

Abstract: The ability to incorporate intracranially injected 14C-labelled leucine into central nervous system (CNS) myelin was studied in developing rats fed a control diet, a diet deficient in vitamin E and a diet deficient both in vitamin E and polyunsaturated fatty acids. The turnover of radioactivity incorporated into myelin and the distribution of radioactivity between the individual proteins of rat CNS myelin at various stages of the deficiency state was studied. Impaired myelin formation was found in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Investigations of chronic vitamin E deficiency produced by feeding rats α-T deficient diets suggested that the CNS was more severely affected than the peripheral nervous system (Towfighi, 1981). Experimental data showing a need for α-T for CNS myelination emerged from studies in rats fed diets that varied in α-T concentrations (Dinesen and Clausen, 1976). Comparative morphometric analysis of cerebellar synapses of young and old rats indicated a role for α-T in preserving synaptic morphology (Bertoni-Freddari et al, 1995;Bertoni-Freddari et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of chronic vitamin E deficiency produced by feeding rats α-T deficient diets suggested that the CNS was more severely affected than the peripheral nervous system (Towfighi, 1981). Experimental data showing a need for α-T for CNS myelination emerged from studies in rats fed diets that varied in α-T concentrations (Dinesen and Clausen, 1976). Comparative morphometric analysis of cerebellar synapses of young and old rats indicated a role for α-T in preserving synaptic morphology (Bertoni-Freddari et al, 1995;Bertoni-Freddari et al, 1984).…”
Section: Introductionmentioning
confidence: 99%